Structural insights into the LCIB protein family reveals a new group of β-carbonic anhydrases - Jin, Shengyang (2017)
Aquatic microalgae have evolved diverse CO2-concentrating mechanisms (CCMs) to saturate the carboxylase with its substrate, to compensate for the slow kinetics and competing oxygenation reaction of the key photosynthetic CO2-fixing enzyme rubisco. The limiting CO2-inducible B protein (LCIB) is known to be essential for CCM function in Chlamydomonas reinhardtii. To assign a function to this previously uncharacterized protein family, we purified and characterized a phylogenetically diverse set of LCIB homologs. Three of the six homologs are functional carbonic anhydrases (CAs). We determined the crystal structures of LCIB and limiting CO2-inducible C protein (LCIC) from C. reinhardtii and a CA-functional homolog from Phaeodactylum tricornutum, all of which harbor motifs bearing close resemblance to the active site of canonical β-CAs. Our results identify the LCIB family as a previously unidentified group of β-CAs, and provide a biochemical foundation for their function in the microalgal CCMs.